Evaluation of microbial-fructo-oligosaccharides metabolism by human gut microbiota fermentation as compared to commercial inulin-derived oligosaccharides - Roupar, Dalila (2022)
The prebiotic potential of fructo-oligosaccharides (microbial-FOS) produced by a newly isolated Aspergillus ibericus, and purified by Saccharomyces cerevisiae YIL162 W, was evaluated. Their chemical structure and functionality were compared to a non-microbial commercial FOS sample. Prebiotics were fermented in vitro by fecal microbiota of five healthy volunteers. Microbial-FOS significantly stimulated the growth of Bifidobacterium probiotic strains, triggering a beneficial effect on gut microbiota composition. A higher amount of total short-chain fatty acids (SCFA) was produced by microbial-FOS fermentation as compared to commercial-FOS, particularly propionate and butyrate. Inulin neoseries oligosaccharides, with a degree of polymerization (DP) up to 5 (e.g., neokestose and neonystose), were identified only in the microbial-FOS mixture. More than 10% of the microbial-oligosaccharides showed a DP higher than 5. Differences identified in the structures of the FOS samples may explain their different functionalities. Results indicate that microbial-FOS exhibit promising potential as nutraceutical ingredients for positive gut microbiota modulation.